Facial Expressiveness in Infants With and Without Craniofacial Microsomia: Preliminary Findings. (May 2018) - Hammal, Zakia; Cohn, Jeffrey F.; Wallace, Erin R.; Heike, Carrie L.; Birgfeld, Craig B.; Oster, Harriet; Speltz, Matthew L.
Objective: To compare facial expressiveness (FE) of infants with and without craniofacial microsomia (cases and controls, respectively) and to compare phenotypic variation among cases in relation to FE. Design: Positive and negative affect was elicited in response to standardized emotion inductions, video recorded, and manually coded from video using the Facial Action Coding System for Infants and Young Children. Setting: Five craniofacial centers: Children's Hospital of Los Angeles, Children's Hospital of Philadelphia, Seattle Children's Hospital, University of Illinois–Chicago, and University of North Carolina–Chapel Hill. Participants: Eighty ethnically diverse 12- to 14-month-old infants. Main Outcome Measures: FE was measured on a frame-by-frame basis as the sum of 9 observed facial action units (AUs) representative of positive and negative affect. Results: FE differed between conditions intended to elicit positive and negative affect (95% confidence interval = 0.09-0.66, P = .01). FE failed to differ between cases and controls (ES = –0.16 to –0.02, P = .47 to .92). Among cases, those with and without mandibular hypoplasia showed similar levels of FE (ES = –0.38 to 0.54, P = .10 to .66). Conclusions: FE varied between positive and negative affect, and cases and controls responded similarly. Null findings for case/control differences may be attributable to a lower than anticipated prevalence of nerve palsy among cases, the selection of AUs, or the use of manual coding. In future research, we will reexamine group differences using an automated, computer vision approach that can cover a broader range of facial movements and their dynamics.